1998
DOI: 10.2337/diab.47.8.1212
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Macrophages From the NOD Mouse Are Defective in the Ability to Present Antigen

Abstract: IDDM results from the destruction of pancreatic beta-cells by autoreactive T-cells that appear to avoid deletion early in development, possibly due to improper interaction with antigen-presenting cells (APCs) resident in the thymus or periphery. In the nonobese diabetic (NOD) mouse, there exists a defect in APC function characterized by its failure to fully mature upon stimulation. The NOD mouse thus provides an excellent model for the investigation of APC dysfunction and development and how these relate to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 29 publications
2
43
1
Order By: Relevance
“…Multiple immune-related genes involving different biological functions, from antigen processing and presentation to T cell activation, migration and apoptosis, have been suggested as candidates for these Idd loci [17]. Nevertheless, several studies reported abnormal APC function in NOD mice, which might be related to the known T cell dysfunction in this strain [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple immune-related genes involving different biological functions, from antigen processing and presentation to T cell activation, migration and apoptosis, have been suggested as candidates for these Idd loci [17]. Nevertheless, several studies reported abnormal APC function in NOD mice, which might be related to the known T cell dysfunction in this strain [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple immune-related genes involving different biological functions, from antigen processing and presentation to T cell activation, migration and apoptosis, have been suggested as candidates for these Idd loci [17]. Nevertheless, several studies reported abnormal APC function in NOD mice, which might be related to the known T cell dysfunction in this strain [18][19][20].We previously identified a region within GAD65, p524-543 (p543), to which spontaneous T cell responses arise in young NOD mice as early as 3-4 weeks of life [1]. Interestingly, this 20mer peptide appeared to be comprised of two distinct determinants: an N-terminal moiety (p524-538 (p524)) and a C-terminal moiety (p530-543 (p530)).…”
mentioning
confidence: 99%
“…NOD/scid IL-2Rg null mice have been defined as immunodeficient mice lacking functional T cells, B cells, and NK cells. Also, these mice have reduced dendritic functions and defective Mf (14)(15)(16)(17). These mice were treated i.p.…”
Section: Methodsmentioning
confidence: 99%
“…12 Also, a developmental defect in splenic macrophages of NOD mouse was found responsible for their inability to process and/or present autoantigens in a tolerogenic fashion, while allowing them to retain the capacity to activate autoreactive T cells in the periphery. 13 These defects in costimulatory molecules might result in insufficient presenting of antigen signals contributing to deficiently activated (suboptimal) T cells unable to undergo negative selection but sufficient to mount autoimmunity. [14][15][16][17] It has been indicated that in NOD mice, the islet-reactive T cells were refractory to CTLA-4 and their ability to escape peripheral regulation might be greatly increased as well.…”
Section: Introductionmentioning
confidence: 99%